Perceptions of antimicrobial stewardship: identifying drivers and barriers across various professions in Canada utilizing a one health approach - McCubbin, Kayley D.; de Jong, Ellen; Smid, Anne-Marieke C.; Ida, Jennifer A.; Bodaneze, Julia; Anholt, R. Michele; Larose, Samantha; Otto, Simon J. G.; Barkema, Herman W. (Frontiers in Public Health, 2023)
Introduction As antimicrobial resistance (AMR) represents a substantial threat to the efficacy of available antimicrobial options, it is important to understand how to implement effective and practical mitigation efforts, including antimicrobial stewardship (AMS), across human, animal, and environmental sectors. Methods A mixed-methods questionnaire was distributed virtually to attendees of the virtual One Health Antimicrobial Stewardship Conference (March 10–12, 2021) and their professional networks. Respondents (n = 81) were largely from the veterinary (75%) or human (19%) health sectors. Qualitative data were analyzed in NVivo using template analysis whereas quantitative data were analyzed in STATA using Kruskall-Wallis tests. The questionnaire asked respondents about their perceptions of AMS, as well as the perceived barriers and drivers of AMS efforts. Results Perceptions of what AMS meant to the respondents personally and their profession as a whole were grouped into 3 main themes: 1) AMS strategies or considerations in antimicrobial prescribing and use; 2) responsibility to maintain health and preserve antimicrobial effectiveness; and 3) reducing antimicrobial use (AMU) as a goal of AMS efforts. Identified AMS barriers had 3 main themes: 1) lack of various prescribing and AMU support mechanisms; 2) shift in prescriber attitudes to drive change; and 3) stronger economic considerations to support shifting prescribing practices. Drivers of AMS had the following themes: 1) leadership to guide change; 2) education to support optimizing AMU; and 3) research to identify best practices and opportunities for action. Across all questions, 2 cross-cutting themes emerged: 1) a One Health understanding of AMS; and 2) blame placed on others for a lack of AMS success. Conclusion Overall, sector-specific, but particularly cross-sectoral AMS drivers and barriers were identified, highlighting the importance of a One Health approach in AMR research and mitigation.